Application of Problem-Based Learning Model in Improving PAI Learning Outcomes in Class XI SMAN 3 Padang - Sardona (BiCED Proceeding, 2024)
This study aims to analyze the improvement of learning outcomes in Islamic Religious Education (PAI) among university students through the implementation of the Student Centered Learning (SCL) method compared to conventional teaching methods. The research method used is a quasi-experimental study with a pre-test and post-test design applied to two different groups. The results show that the implementation of the SCL method has a positive impact on improving the understanding of PAI material compared to conventional methods. Students taught with the SCL approach showed improvements in critical thinking skills, active participation in discussions, and a better understanding of PAI values. Overall, this study recommends the use of the SCL method as an effective alternative to enhance the quality of PAI education in higher education institutions.